O Capital Social nas Políticas Socioambientais: entre a Panacéia e o Bom Uso do Conceito - Fonseca, Igor Ferraz da (Sustainability in Debate, 2010)
The concept of social capital has become the basis of environmental and development policies in contemporary times. However, proliferation of the concept’s use did not translate into substantive change in the effectiveness of those policies. The aim of this paper is to show that the concept of social capital has been used indiscriminately and uncritically in socio-environmental policies. The banalized use of the concept can compromise the efficiency and effectiveness of projects and policies directed to local development, obscuring asymmetries in power relations. Social capital can be useful for the promotion of sustainable development, however this requires a redefinition of the concept’s use that incorporates conflicts and power relations existing in different realities. Thus, the effort should be directed to a better allocation of social capital and not for his “creation” or “promotion”.